An Overview of Information Instruction in Hospital Libraries in Spain (Journal of EAHIL, 2024)
Introduction: Information instruction is essential to providing support for clinical care, teaching and research in hospitals. In the international literature, little has been published about this function of hospital libraries in Spain. This study examines the education activities of Spanish hospitals.Methods: A questionnaire about staff, education activities and institutional recognition was distributed via email to Spanish hospital libraries. The data was analysed in February 2023.Results: 84% of libraries provide education activities. The average number education staff is 1.3. Common instruction topics are database searching, citations, researcher identity and scientific journals (quality, impact and publication standards). 83% of libraries are part of the undergraduate medical curriculum, 67% are involved in graduate medical education, and 30% are part of the institutional research plan.